Interest Analysis of Indonesian Defense Diplomacy in ASEAN Defense Industry Collaboration (ADIC) - Agung Wicaksono (Budapest International Research and Critics University, 2022)
The concept of an anarchic international system dam will certainly force each country to always increase its power capacity. One of the efforts is to realize the independence of the defense industry. Indonesia is a country that has been a victim of an arms embargo because it is dependent on global producing countries. In line with this, ASEAN has a vision to advance its defense industry through the ASEAN Defense Industry Collaboration (ADIC) program. Although ADIC has many obstacles, this is due to the many differences in the supporting characteristics in the defense sector from each ASEAN member country and the principle of the defense cooperation mechanism which cannot be mutually binding. This paper intends to review the interests and what drives as well as the motives for Indonesia to be involved in this defense industry collaboration. Through qualitative research methods and defense diplomacy analysis framework from Inkirawang. This study will analyze the motives for Indonesia's decision to participate in developing defense independence through ADIC cooperation. Indonesia's interests in terms of defense diplomacy are the reason why Indonesia wants to be involved in the ASEAN defense industry collaboration which has many different supporting characteristics in the defense sector.